Development of Differentiated Learning Tools As An Initiator of Independent Learning - Faqih, Muhammad Izzatul; Adriyani, Zuanita; Muna, Khoriyatul (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2023)
AbstractThis research aims to (1) understand the development of differentiated learning tools as initiators of independent learning, (2) assess the feasibility of differentiated learning tools as initiators of independent learning, and (3) determine the effectiveness of learning using differentiated learning tools as initiators of independent learning. The research adopted the Research and Development (R&D) methodology, employing data collection techniques such as documentation, observation, interviews, and questionnaires. The research yielded learning tools in the form of Syllabus (RPS), Lesson Implementation Plan (LKM), authentic evaluation instruments, and instruments for learning styles that are highly suitable according to experts. The effectiveness of the tools was evidenced by significantly high scores with a Sig (2-tailed) value less than 0.05. AbstrakPenelitian ini bertujuan untuk (1) Memahami cara mengembangkan perangkat pembelajaran berdiferensiasi sebagai inisiator merdeka belajar, (2) Mengetahui kelayakan perangkat pembelajaran berdiferensiasi sebagai inisiator merdeka belajar, (3) Mengetahui efektivitas pembelajaran menggunakan perangkat pembelajaran berdiferensiasi sebagai inisiator merdeka belajar. Jenis dari penelitian yang dipakai adalah penelitian Research and Developement (R&D). Teknik pengumpulan data menggunakan dokumentasi, observasi, wawancara, dan angket. Hasil penelitian perangkat pembelajaran berupa RPS, LKM, instrumen evaluasi autentik, dan instrumen untuk gaya belajar yang sangat layak digunakan menurut ahli serta perangkat efektiv dengan nilai yang sangat signifikan ditandai dengan skor Sig (2-tailed) kurang dari 0,05.Kata kunci: Perangkat pembelajaran berdiferensiasi; merdeka belajar